Analisa Pengembangan Fitur Lebih Lanjut dengan Pendekatan Requirement Analysis dan Design Thinking - Perkasa, Ramadhani Tegar; Samopa, Febriliyan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Hospital Management Information System (SIMRS) is an information system that has been widely used in the health service sector. One of the health information systems in Indonesia is SIMRS Medify. This platform is used for management and administration of patient data, scheduling, and hospital administration. However, there is still dissatisfaction with the application. This research aims to analyze and design further feature development in the SIMRS Medify using a requirements analysis and design thinking approach. The requirements analysis approach is used to identify user needs from an ideal and objective perspective. Apart from envisioning and evaluation, the requirements analysis method is also used in the prototyping process. In the next stage, the design thinking method will be used to design new features with an approach focused on the user's emotional perspective which will focus on empathy from what is felt directly. This method will involve empathy, interview, define and ideate. The results of this research are an analysis of further feature development in SIMRS Medify. Not only from an objective perspective or the suitability or completeness of the application, but also from a subjective perspective or user desires.